Infrared Spectroscopic Study on the Modified Mechanism of Aluminum-Impregnated Bone Charcoal. (22nd June 2014) - Li, Hao; Yang, Yufan; Yang, Shuangjun; Chen, Anpu; Yang, Dazuo
Abstract : Fluoride contamination in drinking water is a prominent and widespread problem in many parts of the world. Excessive ingestion of fluoride through water can lead to the high risk of fluorosis in human body. Bone charcoal, with the principal active component of hydroxyapatite, is a frequently used adsorbent for fluoride removal. Many laboratory experiments suggest that the aluminum-impregnated bone charcoal is an effective adsorbent in defluoridation. However, the mechanisms underlying this modification process are still not well understood, which in turn greatly impedes the further studies on other different modified adsorbents. To address this issue, we used the infrared spectroscopy to examine the bone charcoal and the aluminum-impregnated bone charcoal, respectively. The comparative results show that the −OH peak of infrared spectroscopy has been intensified after modification. This significant change helped speculate the modified mechanism of the aluminum-impregnated bone charcoal. In addition, it is found that the hydroxide ion dissociates from hydroxyapatite in the modification process. Such finding implies that the tetrahydroxoaluminate can be combined with the hydroxyapatite and the aluminum ion can be impregnated onto the bone char surface.